Parathyroid Glands New Aspects - Goncu, Beyza; Gensure, Robert (IntechOpen, 2023)
Parathyroid glands regulate the levels of calcium, phosphorus, magnesium, and vitamin D in the human body via the secretion of parathyroid hormone (PTH). There are several disorders that can affect the parathyroid glands. These can be genetic, idiopathic, or iatrogenic and can cause poor quality of life, depression, and anxiety. This book discusses parathyroid glands, the importance of proper detection of PTH, parathyroid gland pathophysiology, bone dynamics and dentistry, and genetic diseases of the parathyroid glands.